PEMENUHAN KEBUTUHAN PENDIDIKAN BAGI PENYANDANG DISABILITAS DI KALIMANTAN SELATAN - Latifa Suhada Nisa (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2019)
Education is one of the people with disabilities’s rights that must be fulfilled by the state. Fulfillment of the educational rights of people with disabilities will provide opportunities for them to become equal with other human beings and no longer be marginalized. The South Kalimantan Provincial Government has at least two legal standings that can be used as a basic in meeting the educational needs of persons with disabilities, namely Governor of South Kalimantan Regulation No. 065 of 2012 concerning the Implementation of Special Education, Inclusive Education, Special Intelligent Children Education and / or Special Talents of Educational Support Institutions; and by holding special education and inclusion in South Kalimantan; and South Kalimantan Province Regional Regulation No. 4 of 2019 concerning Protection and Fulfillment of the Rights of Persons with Disabilities. The fulfillment of the educational needs of persons with disabilities has been carried out by the Regional Government of South Kalimantan through spesific and inclusion ways. To improve the quality of its implementation and services, it is necessary to fulfill school infrastructure, increase the inclusion schools, educators, budget support and the participation of the community and family in understanding the situation and educational rights for persons with disabilities. Abstrak Pendidikan merupakan salah satu hak penyandang disabilitas yang wajib dipenuhi oleh negara. Terpenuhinya hak pendidikan penyandang disabilitas akan memberikan kesempatan bagi penyandang disabilitas untuk menjadi setara dengan manusia lainnya dan tidak lagi menjadi kaum termarjinalkan. Pemerintah Provinsi Kalimantan Selatan telah memiliki setidaknya dua kebijakan yang dapat dijadikan dasar dalam pemenuhan kebutuhan pendidikan bagi penyandang disabilitas, yaitu Peraturan Gubernur Kalimantan Selatan No. 065 Tahun 2012 tentang Penyelenggaraan Pendidikan Khusus, Pendidikan Inklusif, Pendidikan Anak Cerdas Istimewa dan/atau Bakat Istimewa Lembaga Pendukung Pendidikan; dan dengan diselenggarakannya pendidikan khusus dan inklusi di Kalimantan Selatan dan Peraturan Daerah Provinsi Kalimantan Selatan No. 4 Tahun 2019 tentang Perlindungan dan Pemenuhan Hak Penyandang Disabilitas. Pemenuhan kebutuhan pendidikan bagi penyandang disabilitas telah dilakukan Pemerintah Daerah Kalimantan Selatan melalui jalur khusus maupun inklusi. Untuk meningkatkan kualitas penyelenggaraan dan pelayanannya diperlukan pemenuhan sarana prasarana sekolah, penambahan sekolah inklusi, tenaga pendidik, dukungan anggaran dan peran serta masyarakat dan keluarga dalam memahami situasi dan hak pendidikan bagi penyandang disabilitas. Kata Kunci: Pendidikan, Penyandang Disabilitas, Kebijakan Pemerintah